From nucleus to membrane: a subcellular map of the N-acetylation machinery in plants - Pożoga, Marlena; Armbruster, Laura; Wirtz, Markus (International journal of molecular sciences, 2022)
N-terminal acetylation (NTA) is an ancient protein modification conserved throughout all domains of life. N-terminally acetylated proteins are present in the cytosol, the nucleus, the plastids, mitochondria and the plasma membrane of plants. The frequency of NTA differs greatly between these subcellular compartments. While up to 80% of cytosolic and 20-30% of plastidic proteins are subject to NTA, NTA of mitochondrial proteins is rare. NTA alters key characteristics of proteins such as their three-dimensional structure, binding properties and lifetime. Since the majority of proteins is acetylated by five ribosome-bound N-terminal acetyltransferases (Nats) in yeast and humans, NTA was long perceived as an exclusively co-translational process in eukaryotes. The recent characterization of post-translationally acting plant Nats, which localize to the plasma membrane and the plastids, has challenged this view. Moreover, findings in humans, yeast, green algae and higher plants uncover differences in the cytosolic Nat machinery of photosynthetic and non-photosynthetic eukaryotes. These distinctive features of the plant Nat machinery might constitute adaptations to the sessile lifestyle of plants. This review sheds light on the unique role of plant N-acetyltransferases in development and stress responses as well as their evolution-driven adaptation to function in different cellular compartments.
Gesehen am 31.01.2023